Basic psychological needs and subjective well-being in portuguese older people - Couto, Nuno (2020)
The aim of this study is the validation of the Portuguese version of the Basic Need Satisfaction General Scale (BNSG-S) in a sample of Portuguese elderly, and analyze through a structural equations model the effect of the Portuguese elderly individuals’ global perception about the satisfaction of basic psychological needs on subjective well-being. Two samples of Portuguese elderly people aged between 60 and 90 years old were considered in this study. Results revealed that they Model 3 of the BNSG-S (three factors, 11 items) adjusted to the data a (χ² = 103.16, df = 41, SRMR = .05, TLI = .90, CFI = .93, RMSEA = .07, 90% CI = .05-.08). Additionally, structural model analysis, showed a positive and significante ffect between satisfaction of basic psychological needs and subjective well-being. In sum we concluded that the Portuguese version of the BNSG-S can be used as a means to evaluate the satisfaction of the basic psychological needs of the older population and, their satisfaction, has a positive effect on subjective well-being in the Portuguese older population.